MOTIVASI WISATAWAN PADA OBJEK WISATA KAMPUNG SENI, KOTA BATAM, KEPULAUAN RIAU - Ichwansyah, Wian Oktaliani; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research began with the results of observations made by the researcher. Researchers found problems that occurred in the Batam City Arts Village, especially regarding the reasons that made tourists want to visit the Art Village. This research was conducted with the aim of knowing the motivation of tourists at the Art Village tourist attraction in Batam City. This research uses a descriptive qualitative. Data collection techniques were carried out using observation, documentation, and interviews by interviewing 4 informants. Keywords: Batam City Arts Village, Tourist